Pengaruh Kepadatan Kandang Yang Berbeda Terhadap Produktivitas Telur Puyuh (Cortunix Cortunix Japonica) Pada Fase Layer: The Effect Of Different Cage Densities On Quail Egg Productivity (Cortunix Cortunix Japonica) In The Phase Layer - Wardana, Yuda; Suhadi, Miki; Wati, Novi Eka (Fakultas Peternakan Universitas Tulang Bawang, 2025)
This research aims to determine the effect of different cage densities on Quail Day Product (QDP), average egg weight and Egg Mass in quail (Cortunix Cortunix Japonica). This research was conducted on August 17, 2024 - September 21, 2024 at Mr. Suwarto's Cage. In Palas Jaya Village, Palas District, South Lampung Regency, Lampung Province. The material of this study was quail (Cortunix Cortunix Japonica) as many as 360 heads aged 42 days in a baterray cage with a size of 100 cm x 50 cm. The method used in this study was a completely randomized design (CRD) with 4 treatments and 5 replicates. The treatment of this study was different cage densities, namely P1 = density of 12 quails, P2 = density of 16 quails, P3 = density of 20 quails, and P4 = density of 24 quails. The data were tabulated using ANOVA, if there was a significant difference, it would be followed by Duncan's test. The results showed that different cage densities in quail (cortunix cortunix japonica) were real effect (P<0.05) to the average egg weight and egg mass (Egg Mass) but not real effect (P>0.05) to Quail Day Product (QDP). The most optimal cage density in quail egg productivity is the P1 treatment with a quail population of 12 birds which shows the average value of QDP (85,40%), the average egg weight (10,14 grams/grain), and the value of Egg Mass (8,68 grams/head/day). Keywords: Average egg weight, Egg mass, Cage Density, Quail (Cortunix Cortunix Japonica), , Quail Day Product (QDP)